EXCEPTION OF POWER OR OFFICIAL AUTHORITIES OF A LAW ENFORCEMENT OFFICER: CRIMINAL AND LEGAL CHARACTERISTICS OF THE ORIGINAL COMMUNITY - Lykhova, Sofiia; Komanetska, Viktoriia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: qualification of a criminal offense «Exception of power or official authorities by a law enforcement officer», criminal-legal characteristics of the offense and features of qualification and development of recommendations for the investigation of this criminal offense. Research methods: a set of general and special methods of scientific knowledge – terminological, logical-semantic, functional, system-structural, logical-normative. Results: the law enforcement officer is aware that he is using his official position against the interests of the service, he is also aware that when exceeding power, he clearly goes beyond the powers granted, which determines the specifics of this criminal offense. An attempt has been made by the legislator to single out certain special types of exception of power or official authorities from the abuse of power or official position. Discussion: it is emphasized that the criminal nature of the actions of a law enforcement official in exception of power or official authorities is expressed in the fact that the official commits an act in the service that is not within its competence. This is the fundamental difference between this criminal offense and abuse of power or official authorities, in which an official, within his powers defined by law, uses them against the interests of the service. Unlike the general abuse of power or official position (Article 364 of the Criminal Code of Ukraine), exception of power or official authorities cannot be manifested in inaction. Its objective side is characterized only by the commission of an action by an official. Exception of power or official authorities by a law enforcement officer to one degree or another exists in any society. Consider this phenomenon from the standpoint of the sociology of deviant behavior. Deviant behavior is an act, human activity, social phenomenon that does not meet the existing norms, stereotypes, patterns of behavior in this society.